Effect of Adding Dibutyltin Dilaurate on the Quality of Polyurethane Paint for Applications in the Automotive Industry - Fitriani, Sri Endah; Puspasari, Ifa; Elisa Kusrini (International Journal on Advanced Science, Engineering and Information Technology, 2024)
In the automotive paint industry, the paint is attached by spraying, followed by a drying process using a baking oven process. For bumpers made from polypropylene (PP) plastic, the oven drying temperature is 80°C. The drying process is often difficult because it requires low temperatures and extended drying times. Therefore, additional raw materials (additives) are needed, which function as catalysts to speed up the drying process. Dibutyltin dilaurate (DBTDL) is an organotin catalyst used in the paint industry. This research aimed to investigate the effect of DBTDL addition on the properties of polyurethane paint used in the automotive industry. The variables of this research include concentration, temperature, and drying time. The properties tested were hardness, adhesion, and gloss. The research method consisted of three stages, namely the preparation stage, application stage, and testing stage. The research results found that the best hardness was obtained at temperatures of 80°C and 90°C, concentrations of 0.2% and 0.3%, and drying times of 25 minutes and 30 minutes. The adhesion test showed 100% results for all samples except at temperatures of 80°C and 90°C, a concentration of 0.3%, and a drying time of 30 minutes. The gloss test results showed a value of more than 90%. From the results of hardness, adhesion, and gloss tests, it can be concluded that the best condition was achieved at a concentration of 0.2% with a drying time of 30 minutes and a temperature of 80-90°C.